IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM PEMBENTUKAN KARAKTER SISWA - Dr. Mardyawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
The educational process can not be separated from philosophy and the nation in which the educational process takes place. So lately the issue of changes and improvements in education sector in Indonesia sticking to the surface, not only in the general education pathway, but all paths and levels of education. As evidence of major changes in the policy development of the education sector is the reform of the education sector in terms of improving the quality of teachers. Education is the process of delivering knowledge to develop the whole person, who has beliefs, attitudes and life skills in order to achieve happiness in life. As is understood that there are three aspects contained in the concept of education, namely the delivery process, the knowledge or the material as well as human beings. One of which is a factor in shaping the character of children is culture, or culture by planting the value of awareness of diversity (plurality), Equality (equality), humanity (humanity), justice (justice), and the value of democracy (democration values), in a variety of social activities, To apply these values ​​and education, into its entrance. This value is called the value of multiculturalism and the value is not also a value that the mandated curriculum in 2013 which is termed character values.